2016
DOI: 10.1016/j.quascirev.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Ice stream retreat following the LGM and onset of the west Greenland current in Uummannaq Trough, west Greenland

Abstract: Citation for published item:heldonD gF nd tenningsD eF nd endrewsD tFF nd ¡ y gofighD gF nd rognD uF nd howdeswellD tFeF nd eidenkrntzD wFEF @PHITA 9se strem retret following the vqw nd onset of the west qreenlnd urrent in ummnnq roughD west qreenlndF9D uternry siene reviewsFD IRU F ppF PUERTF Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
88
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(101 citation statements)
references
References 96 publications
13
88
0
Order By: Relevance
“…In the Laptev Sea, this species has been connected to Atlanticderived water from ∼ 15.4 ka onwards (Taldenkova et al, 2010). AW presence is also inferred prior to ∼ 14 ka off West Greenland (Sheldon et al, 2016a). At the margin of the Arctic Ocean, north of Svalbard, C. neoteretis showed high abundances from at least 24 ka onwards (Wollenburg et al, 2004).…”
Section: The Role Of Atlantic Water In the Deglaciation History Of Thmentioning
confidence: 74%
“…In the Laptev Sea, this species has been connected to Atlanticderived water from ∼ 15.4 ka onwards (Taldenkova et al, 2010). AW presence is also inferred prior to ∼ 14 ka off West Greenland (Sheldon et al, 2016a). At the margin of the Arctic Ocean, north of Svalbard, C. neoteretis showed high abundances from at least 24 ka onwards (Wollenburg et al, 2004).…”
Section: The Role Of Atlantic Water In the Deglaciation History Of Thmentioning
confidence: 74%
“…Along the SE margin, the retreat from the outer to inner shelf is highly asynchronous, with the retreat from the outer Kangerdlugssuaq trough around 17.8 kyr BP (dark blue triangle, Fig.1) (earlier than from the central east), reaching the 150 inner fjord by 11.8 kyr BP at Kangerdlugssuaq (open blue triangle, Fig.1), and by 10.8 kyr BP at Sermilik (red cross, Fig.1). It is suggested that the timing of retreat across this region is strongly influenced by the warm incursion of Irminger current The SW region of Greenland, around Disko Bugt and Uumannaq trough is one of the more extensively studied region of the ice sheets, with a range of observational data confirming the 155 grounding of the ice sheet to the continental shelf break (Winsor et al, 2015;Sheldon et al, 2016;Jennings et al, 2014;Cofaigh et al, 2013). The retreat from the outer shelf (cluster of red triangles, Fig.1) between 19.3-18.6 kyr BP is inferred to have been driven by either a change in sea level and/or an ongoing gradual rise in boreal summer insolation rather than changes in ocean temperatures.…”
Section: Observational Datamentioning
confidence: 98%
“…The question of whether a change in sea level could initiate such a retreat is just one aspect that the use of a RSL forcing in this study will examine. The retreat from the outer shelf edge in the vicinity of the Uumannaq fjord (cluster of green triangles, Fig.1) was later, after 14.9 kyr BP, reaching the outer Uumannaq trough by 10.8 kyr BP (Sheldon et al, 2016). 165…”
Section: Observational Datamentioning
confidence: 99%
“…The SW region of Greenland, around Disko Bugt and the Uumannaq Trough, is one of the more extensively studied regions of the ice sheet, with a range of observational data confirming that the ice sheet grounded out onto the continental shelf break (Cofaigh et al, 2013;Jennings et al, 2014;Sheldon et al, 2016;Winsor et al, 2015). The retreat from the outer shelf (cluster of red triangles, Fig.…”
Section: Observational Datamentioning
confidence: 98%
“…The retreat from the outer shelf edge in the vicinity of the Uumannaq Fjord (cluster of green triangles, Fig. 1) was later, after 14.9 ka BP, reaching the outer Uumannaq Trough by 10.8 ka BP (Sheldon et al, 2016). Against this background of geological evidence, we evaluated our model results as presented in Sect.…”
Section: Observational Datamentioning
confidence: 99%